Achyranthes bidentata Polypeptide Protects Schwann Cells From Apoptosis in Hydrogen Peroxide-Induced Oxidative Stress - Li, Meiyuan; Zhu, Ye; Peng, Wenqiang; Wang, Hongkui; Yuan, Ying; Gu, Xiaosong (Frontiers in Neuroscience, 2018)
ABPPk, the active ingredient separated from Achyranthes bidentata polypeptides (ABPP), is a traditional Chinese medicine with multiple pharmaceutical properties. In this study, we investigated the molecular mechanisms of ABPPk in protecting Schwann cells (SCs) from hydrogen peroxide (H2O2)-induced cell apoptosis. The viability of SCs pretreated with ABPPk was elevated significantly by MTT assay estimation. Meanwhile the apoptosis of SCs was reduced which was showed in Flow cytometry and TUNEL analysis. Futhermore, the addition of ABPPk also increased the activities of SOD and GSH accompanied with a decrease in MDA and LDH activities. According to Western blot analysis, the up-regulation of Bcl-2, also down-regulation of Bax and cleaved caspase-3 were demonstrated in SCs which ABPPk pretreated. Futher research showed that the ABPPk pretreatment can activate PI3K/AKT and ERK1/2 pathways in SCs. To sum up, the results in our study suggested that ABPPk protectd SCs from H2O2-induced oxidative damage by reducing the expression of apoptotic molecules and enhancing the activities of antioxidant enzymes, which inhibited the apoptosis of SCs modulated by PI3K/AKT and ERK1/2 signaling pathways. In our perspectives, ABPPk as an active factor with its anti-oxidative activities has potential and promosing therapeutic effects on the prevention of neurologic disorders.